User conceptions of trustworthiness for digital archival documents. (30th January 2015) - Donaldson, Devan Ray; Conway, Paul
Abstract : Trust is the most important characteristic of digital repositories designed to hold and deliver archival documents that have persistent value to stakeholders. In theoretical models of trust in information, the concept of trustworthiness is emerging as both fundamentally important and understudied, particularly in the domain of digital repositories. This article reports on a qualitative study designed to elicit from groups of end users components of trustworthiness and to assess their relative importance. The study draws on interview data from 3 focus groups with experienced users of the Washington State Digital Archives. Utilizing thematic analysis and micro‐interlocutor analysis to examine a combination of interview transcripts and video recordings, the study provides a realistic picture of the strength and character of emergent themes that underpin the more general concept of trustworthiness. The study reinforces the centrality of trustworthiness at the individual document level, but calls into question the formulation of trustworthiness as a concept in Kelton, Fleischmann, and Wallace's (2008) Integrated Model of Trust in Information.